Can scientists and policy makers work together?. Issue 8 (14th July 2005) - Choi, Bernard C K; Pang, Tikki; Lin, Vivian; Puska, Pekka; Sherman, Gregory; Goddard, Michael; Ackland, Michael J; Sainsbury, Peter; Stachenko, Sylvie; Morrison, Howard; Clottey, Clarence
Abstract : This paper addresses a fundamental question in evidence based policy making—can scientists and policy makers work together? It first provides a scenario outlining the different mentalities and imperatives of scientists and policy makers, and then discusses various issues and solutions relating to whether and how scientists and policy makers can work together. Scientists and policy makers have different goals, attitudes toward information, languages, perception of time, and career paths. Important issues affecting their working together include lack of mutual trust and respect, different views on the production and use of evidence, different accountabilities, and whether there should be a link between science and policy. The suggested solutions include providing new incentives to encourage scientists and policy makers to work together, using knowledge brokers (translational scientists), making organisational changes, defining research in a broader sense, re-defining the starting point for knowledge transfer, expanding the accountability horizon, and finally, acknowledging the complexity of policy making. It is hoped that further discussion and debate on the partnership idea, the need for incentives, recognising the incompatibility problems, the role of civil society, and other related themes will lead to new opportunities for further advancing evidence based policy and practice.